Construction of Ternary Heterojunction g-C3N4 /BiVO4 /GQDs Nanocomposite and Its Methylene Blue Photodegradation Performance - Arieveali, Heroldinho; Setyaningtyas, Tien; Riyani, Kapti; Riapanitra, Anung (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Ternary heterojunction g-C3N4/BiVO4/GQDs (CBG) composite photocatalysts were successfully made by high-temperature solidstate method. The prepared CBG photocatalyst was used to degrade the methylene blue (MB) solution under the simulation of visible light irradiation. The analysis of photocatalytic activity was carried out in the parameters of mass variation of composite components, pH of MB solution, and kinetic rate measurement. The results showed that the adsorption-photocatalysis synergy effect occurred at its best in CBG-20 samples with pH 9 in MB solution with a degradation kinetic rate following the pseudo-first order within 150 min of removal time as the optimum condition that could degrade MB by 94.81%. The result showed that the photocatalytic activity of theternary composite was higher than that of pristine g-C3N4, BiVO4, or the binary composite of g-C3N4/BiVO4. Trapping experiments results support the direct dual Z-scheme which shows that ·O2- is the most significant radical for the photocatalytic degradation of MB. The prepared ternary composites show outstanding application prospects in wastewater treatment.